ON THE APPROXIMATION OF FUNCTIONS OF THE HÖLDER CLASS BY BIHARMONIC POISSON INTEGRALS - Kharkevych, Yurii I.; Zhyhallo, Kostiantyn M.; Харкевич, Юрій Іліодорович; Жигалло, Костянтин Миколайович (Ukrainian Mathematical Journal, 2000)
We determine the exact value of the upper bound of the deviation of biharmonic Poisson integrals from functions of the Hölder class.